A Kind of Quaternary Sequences of Period 2pmqn and Their Linear Complexity. (17th March 2020) - Wang, Qiuyan; Wu, Chenhuang; Yang, Minghui; Yan, Yang
Abstract : Sequences with high linear complexity have wide applications in cryptography. In this paper, a new class of quaternary sequences over F 4 with period 2 p m q n is constructed using generalized cyclotomic classes. Results show that the linear complexity of these sequences attains the maximum.